Konstruksi Identitas Pelari Digital: Manajemen Kesan Pengguna Strava dalam Perspektif Dramaturgi - Lubnatul Syarbanu; Meistra Budiasa (Lembaga Teewan Journal Solutions, 2026)
This study examines the construction of digital identity among runners who use Strava through Erving Goffman's dramaturgical perspective, focusing on the management of front stage and back stage in the practice of sharing running activities in digital space. The study aims to analyze how urban runners who use Strava construct their digital identity through self-presentation, impression management, and digital social interaction such as kudos and comments. This research applies a qualitative approach with a descriptive research type. Data were collected through in-depth interviews with eight informants who are active Strava users in Jakarta, nonparticipant observation of the informants' Strava accounts, and documentation of running activity uploads. Data were analyzed using the interactive model of Miles and Huberman and interpreted through Goffman's dramaturgical theory. The results show that the use of Strava is not merely understood as a sports-tracking application, but also as a medium of self-documentation and self-evaluation, a space for self-presentation, and an arena of impression management. The main findings reveal that Strava users selectively display their best-performing activities on the front stage (public uploads) and conceal negative experiences such as fatigue, injury, or failure to reach targets on the back stage. Social interactions in the form of kudos and comments function as a form of social recognition that reinforces motivation, although not all users regard them as determinants of identity. Authenticity remains a value strongly upheld by the majority of users, who prefer to display genuine progress rather than manipulate their performance. This study concludes that the construction of runner identity on Strava is the result of negotiation between personal experience, impression management, and social response, positioning Strava as a digital space that not only records sporting activity but also becomes an arena for the formation of meaning and social identity.